The Relationship between Ergometric Treadmill or Bicycle Performance and Isokinetic Trunk Strength – A Retrospective Analysis - Geißler, Daniel; Lison, Andreas; Schulze, Christoph (International Journal of Sports Medicine, 2022)
The relationship between trunk strength and athletic performance is well known. In the past, trunk strength and athletic performance were measured in field tests. Previous studies encouraged sport-specific analyses. The goal of this study was to investigate whether there is a relation between ergometrically measured treadmill or bicycle endurance and isokinetic trunk strength. This retrospective analysis included 1334 bicycle and 1838 treadmill ergometry examinations in 1149 subjects. Bicycle and treadmill ergometer performance were analysed in relation to isokinetic trunk strength. Statistics were performed by Pearson correlation and mixed or generalised linear models. Higher treadmill and bicycle power correlated with higher isokinetic trunk strength, with highest absolute trunk strength in the treadmill group. For both running and cycling endurance, a positive correlation with trunk strength could be quantified in regression models. Increased ergometry endurance and lower flexion/extension ratios are connected weakly. Ergometry performance had the strongest correlation with extension trunk strength (r=0.312–0.398 for bicycle ergometry and r=0.168–0.229 for treadmill ergometry, p<0.001). We encourage prospective studies using both kinds of ergometry to evaluate the effect of trunk strengthening to enhance sport-specific endurance performance. Weight-adapted trunk strength values showed overall greater correlation to trunk strength and we recommend the use of weight-adapted values.
Keywords: trunk strength; endurance; ergometry; athletic performance; training